The first pediatric case of tularemia in Korea: manifested with pneumonia and possible infective endocarditis - Jung Sook Yeom; Kyuyol Rhie; Ji Sook Park; Ji-Hyun Seo; Eun Sil Park; Jae-Young Lim; Chan-Hoo Park; Hyang-Ok Woo; Hee-Shang Youn (Korean Pediatric Society, 2015)
Tularemia is a potentially severe zoonotic disease caused by Francisella tularensis. A lack of awareness about tularemia can be embarrassing and could result in delayed treatment because of improper diagnosis. The diagnosis of tularemia is difficult, because the infections are rare and the clinical spectrum is broad. As only 1 adult case has been reported in Korea thus far, pediatricians in Korea may be unfamiliar with tularemia. We report our experience with a 14-year-old male adolescent with tularemia who presented with atypical pneumonia and possible infective endocarditis. Although the infectivity and mortality rates for tularemia are very high if left untreated, we did not suspect tularemia in this case until the incidental isolation of F. tularensis. The present case suggests that clinicians in Korea should be more aware of tularemia. This case also suggests that tularemia should be considered in undetermined cases of atypical pneumonia or acute febrile illness without local signs.